THE DYNAMICS OF DRAFTING AND REVISING LEGISLATION IN INDONESIA: RESPONDING TO SOCIAL, ECONOMIC, AND TECHNOLOGICAL CHANGES THROUGH A PARTICIPATORY AND CONSTITUTIONAL APPROACH – A LITERATURE REVIEW - Gunawan Widjaja (INJOSEDU: International Journal of Social and Education, 2025)
This study discusses the dynamics of drafting and revising legislation in Indonesia, emphasising the importance of regulations that are responsive to social, economic, and technological changes. Through a literature review, this study shows that non-adaptive regulations often lag behind the realities of society, creating a gap between legal norms and public needs. On the other hand, accelerated legislation without in-depth review can lead to controversy and public resistance, as seen in various cases of important law formation in Indonesia over the past two decades. This study emphasises that responsive regulations do not only depend on temporal aspects, namely the speed of responding to change, but also substantive aspects, namely the compatibility between the content of the law and public interests, principles of justice, and global developments. A participatory approach provides space for the public to be involved in every stage of legislation, while constitutional principles ensure that legislation is in line with the basic values of the 1945 Constitution, upholding the protection of human rights, legal certainty, and social justice. The results of the study confirm that the success of legislation in Indonesia is determined by the ability to integrate regulatory responsiveness with substantive public participation and respect for constitutionalism. With a legislative model that is increasingly open, inclusive, and adaptive, it is hoped that Indonesia will be able to build a legal system that is relevant, legitimate, and capable of facing the challenges of globalisation and technological transformation without sacrificing democratic stability.